Understanding Perceived Risks in Proximity Mobile Payment Adoption in South Africa and the Mediating Effect of Perceived Value - Humbani, Michael (International Review of Management and Marketing, 2021)
The purpose of this study is to empirically test the relationship between perceived risk factors and adoption of proximity mobile payments, and to explore the mediating effect on perceived value. Using a descriptive research design, an online self-administered questionnaire was used to collect data from 297 users of proximity mobile payments in South Africa. Confirmatory factor analysis using Amos version 27 was used to analyse the data. The assessment of the path coefficients indicates a statistically significant relationship between psychological insecurity and adoption of proximity mobile payments. Further analysis indicated that perceived value fully mediates the relationship between psychological insecurity and adoption of proximity mobile payments. To the best knowledge of the author, this study is the first to provide empirical evidence of the mediating effect of perceived value on the relationship between perceived risk factors and adoption of proximity mobile payments in an emerging economy. Therefore, the study makes valuable contributions to academicians and practitioners in quest for safe proximity mobile payment apps. Keywords Perceived risks adoption intention, proximity mobile payments, perceived value theory JEL Classifications: M31, L81 DOI: https://doi.org/10.32479/irmm.11814